Analisis Implementasi Menu Engineering dalam Upaya Meningkatkan Volume Penjualan Pada Sally Bakery - Suwandy, Sally; Facrureza, Dewantara (Jurnal Ilmiah Pariwisata; Vol 28 No 3 (2023): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v28i3.1753, 2023)
The bakery industry is one of the food and beverage industries that is increasingly popular on both large and small scales or is usually called a home industry. One of the home industries operating in the bakery sector is Sally Bakery which is located in Harapan Indah, Bekasi. This research was motivated by sales instability so that there was no significant increase in sales volume at Sally Bakery. A food business evaluates the menu at each certain period so that the food business can provide stable profits. Based on these conditions, this research aims to analyze the menu using the menu engineering method. The research was carried out from March 2022 to February 2023. The analysis methods used were contribution margin analysis, menu mix percentage analysis, and menu engineering workshop analysis. Based on analysis for 12 months, results were obtained from 27 menus, namely the star category consisting of 11 menus with a percentage of 40.47%, the plowhorse category consisting of 8 menus with a percentage of 29.63%, the puzzle category consisting of 7 menus with a percentage of 25.93%, and the dog category consists of 1 menu with a percentage of 3.70%. Keywords: Menu Engineering, Menu Mix Percentage, Contribution Margin